LATVIAN MUSIC CULTURE IN THE 1920S –1930S AND MODERNISM. THE NARRATIVES OF THE PRESS AND CONTEXTS (Mūzikas akadēmijas raksti, 2024)
This publication aims to trace the ways 20th century modernism reached Latvia during the two decades of the 20th century interwar period. The main source for the research was the Latvian press of the 1920s and 1930s.The discourse prevailing in Latvian musicology is that musical modernism had almost no impact on Latvian music until the very end of the 20th century, and the techniques, idioms and paradigms of 20th century modernism found reflection in Latvian music only sporadically and unsystematically. Thus, it was quite a surprise to realise how broad and detailed the narrative on musical modernism actually was in Latvian press of the period.Firstly, it included stylistic and aesthetical analyses of contemporary music, the first publications on the subject to be found as early as of 1921. (It should be noted that only a year earlier the Freedom Battles, fighting both the Red Army and the German established Bermondt-Avalov army had ended in Latvia.) It also included information on international activities related to modern music, such as reports on the festivals of the International Society for Contemporary Music (ISCM), the organisation’s strategies and tactics. Publications by renowned representatives of modernity can be found, for example, reports of composer Egon Wellesz (1885–1774) on the status quo of contemporary music and on the ISCM festivals of 1925.